Implementation of Kampus Mengajar on The Program of Kampus Merdeka Merdeka Belajar in Developing Students’ Speaking Skill At English Education Department of Bosowa University - Muhammad, Achmad Fajar; Nurwidyayanti; A.Rizal (MultiTech Publisher, 2024)
This study aims to identify the implementation of Kampus mengajar on the program of Kampus Merdeka-Merdeka Belajar in developing students' speaking skills. This research was conducted at the University of Bosowa. The population in this study were English Education students who graduated from the Teaching Campus program. The total population is 12 students. In sampling, the English Education Study Program uses a saturated sample technique. Research data were collected using a questionnaire. In analyzing the data, the researcher used quantitative data analysis. The results showed that the existence of the Kampus Mengajar program, which was attended by students, had an effect on increasing the speaking ability of students who took part in this program. The results showed that the existence of the Kampus Mengajar program which was attended by students had an effect on increasing the speaking ability of students who took part in this program.